2017
DOI: 10.1039/c7nj02272g
|View full text |Cite
|
Sign up to set email alerts
|

Cu@furfural imine-decorated halloysite as an efficient heterogeneous catalyst for promoting ultrasonic-assisted A3and KA2coupling reactions: a combination of experimental and computational study

Abstract: A novel catalyst was synthesized by functionalization of HNTs with (3-chloropropyl) trimethoxysilan, thiosemicarbazide and furfural and incorporation of copper species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 72 publications
1
22
0
Order By: Relevance
“…Furthermore, FT‐IR spectrum of HNTs‐T exhibited a typical band at 1374 cm ‐1 corresponding to the stretching mode of C‐O which shifts to the smaller wave numbers (1365 cm ‐1 ) after immobilization of Ag NPs in Ag@HNTs‐T. Worthy to mention that the similar comparative interpretations between FT‐IR bands and calculated metal‐ligand interactions are generally considered and reported, previously …”
Section: Resultssupporting
confidence: 59%
“…Furthermore, FT‐IR spectrum of HNTs‐T exhibited a typical band at 1374 cm ‐1 corresponding to the stretching mode of C‐O which shifts to the smaller wave numbers (1365 cm ‐1 ) after immobilization of Ag NPs in Ag@HNTs‐T. Worthy to mention that the similar comparative interpretations between FT‐IR bands and calculated metal‐ligand interactions are generally considered and reported, previously …”
Section: Resultssupporting
confidence: 59%
“…In the course of our research on heterogeneous catalysis, recently we reported the utility of CDNS and natural clays for immobilizing catalytic active species . In this line, it was found that the hybridization of inorganic supports with CDNS can lead to an improvement of the catalytic performance of the resulting catalyst .…”
Section: Introductionmentioning
confidence: 99%
“…Halloysite is an emerging nanofiller for the fabrication of smart nanocomposites with specific functionalities useful for several technological purposes, such as anti-corrosion coatings [1][2][3], food packaging [4][5][6], remediation [7][8][9][10][11], catalysis [12][13][14][15], tissue engineering [16][17][18], preservation of art-works [19][20][21], and antimicrobial protection [22,23]. Recent biological studies (by means of both in vivo and vitro tests) proved that halloysite exhibits a low toxicity [24][25][26].…”
Section: Introductionmentioning
confidence: 99%